1984
DOI: 10.1007/bf01309300
|View full text |Cite
|
Sign up to set email alerts
|

Mouse hepatitis virus strain — Related patterns of tissue tropism in suckling mice

Abstract: The pattern of tissue tropism for several prototype and uncharacterized strains of mouse hepatitis virus (MHV) was studied by intranasal inoculation of each virus strain into groups of neonatal Swiss mice under otherwise identical conditions. Mice were killed at intervals up to 18 days after inoculation, and their tissues were examined for the presence of MHV antigen by indirect immunofluorescence. Two patterns of infection were apparent. Prototype MHV strains 1, 3, A59, JHM, S and uncharacterized MHV strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 20 publications
3
55
0
Order By: Relevance
“…In susceptible hosts, they spread via viraemia, via lymphatics or along olfactory neural pathways to multiple organs of the body, particularly liver and lymphatic organs. However, while these viruses infect the lymphoid tissues of the intestine, they only minimally infect enterocytes (Barthold & Smith 1984). The terms 'neurotropic' or 'hepatotropic', even though still in use, merely describe which tissue is affected most by strains which have often been experimentally selected for such tropism.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In susceptible hosts, they spread via viraemia, via lymphatics or along olfactory neural pathways to multiple organs of the body, particularly liver and lymphatic organs. However, while these viruses infect the lymphoid tissues of the intestine, they only minimally infect enterocytes (Barthold & Smith 1984). The terms 'neurotropic' or 'hepatotropic', even though still in use, merely describe which tissue is affected most by strains which have often been experimentally selected for such tropism.…”
mentioning
confidence: 99%
“…Neurotropic and hepatotropic isolates were described and emphasized but their affinity to liver or brain were by no means absolute (Barthold & Smith 1984). Pathogenesis studies in mice experimentally infected by a natural route (oronasal inoculationl, however, revealed that these MHV strains all replicated in the upper respiratory tract as a common site of primary replication (Barthold & Smith 1984). In susceptible hosts, they spread via viraemia, via lymphatics or along olfactory neural pathways to multiple organs of the body, particularly liver and lymphatic organs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To increase our understanding of the virus-cell interactions that occur during MHV infection, the replication of several strains of MHV was compared in various cell lines of murine origin. It has been proposed that MHV is divided into two overlapping biotypes, termed polytropic and enterotropic [2], but the molecular basis for these biotypes is not yet known. In this investigation, we had expected that enterotropic strains would replicate preferentially in the colon carcinoma cell line CMT-93, because this cell line was assumed to provide an environment comparable to that in vivo, but no substantial differences between polytropic and enterotropic strains in viral replication were observed in any of the cell lines tested.…”
Section: Discussionmentioning
confidence: 99%
“…MHV-A59 is hepatotropic, and the infection of susceptible mice leads to the destruction of liver parenchymal and Kupffer cells . Howe v er, there is considerable overlap of target tissues bet ween these strains of v i rus (Barthold and Smith, 1984). For example, intracerebral inoculation of MHV-A59 in weanling mice also causes demyelinating disease, although the target cells in this case are non-neuronal cells (Lavi, et al, 1984) .…”
Section: Coronaviruses and Mevmentioning
confidence: 99%